Hubungan Fear of Negative Evaluation dengan Perfeksionisme pada Mahasiswa Program Studi Diploma Tiga Keperawatan Universitas Abulyatama - Virah Matina; Syukriadi Syukriadi; Nurul Sakdah (Inovasi Kesehatan Global, 2025)
Perfectionism is a personality trait that reflects high standards to be perfect, but at excessive levels. The feeling of perfectionism leads to students' mental health. One of the factors influencing perfectionism is the fear of negative evaluation, which is the fear of negative judgments from others. This study aims to investigate the correlation between fear of negative evaluation and perfectionism in students of the Diploma III Nursing Study Program at Universitas Abulyatama. The research is conducted from April 26th to May 9th, 2025. This study is a correlational quantitative design with a cross-sectional approach. The population consisted of 554 students. Of 85 respondents chosen as the sample, who were selected using a proportional random sampling technique. The data was gathered by using the Brief Fear of Negative Evaluation (BFNE) questionnaire to measure Fear of Negative Evaluation and the Perfectionism Inventory (PI) to measure perfectionism. Then, the data was analyzed by using univariate and bivariate analysis. The results prove that off out 85 respondents, the majority of students who were in the medium category of Fear of Negative evaluation were 63 respondents (74.1%), high category of fear of negative evaluation were 22 respondents (25,9%), medium category of perfectionism were 54 respondents (63,5%) and, high category of perfectionism were 31 respondents (36,5%). The result of the Chi-Square test indicates a p-value = 0,005. It can be concluded that there is a correlation between fear of negative evaluation and perfectionism among the students of the Diploma III Nursing Study Program at Universitas Abulyatama. This study is expected to serve as a reference for students and educational institutions in providing support for mental health and the development of students' character. By addressing fear of negative evaluation, universities can help students build healthier perspectives, improve self-acceptance, and balance high achievement with psychological well-being.